2010
DOI: 10.1159/000318787
|View full text |Cite
|
Sign up to set email alerts
|

CKD Patients: The Dilemma of Serum PTH Levels

Abstract: Recent observational studies of patients with stage 3–5 chronic kidney disease (CKD) not undergoing dialysis have shown that even slight increases in parathyroid hormone (PTH) levels are associated with an increased cardiovascular risk, regardless of the serum levels of calcium and phosphorus and vitamin D therapy. These studies suggest paying particular attention to monitoring PTH levels from the early stages of CKD, and preventing any mineral metabolism disorders that may trigger the excessive synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Parathyroid hormone (PTH) levels are associated with increased cardiovascular risk in CKD patients [21]. miR-223 presented a strong negative correlation with PTH, while miR-155 was positively correlated with PTH.…”
Section: Resultsmentioning
confidence: 99%
“…Parathyroid hormone (PTH) levels are associated with increased cardiovascular risk in CKD patients [21]. miR-223 presented a strong negative correlation with PTH, while miR-155 was positively correlated with PTH.…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of phosphorus, FGF-23, and parathyroid hormone is associated with worsening kidney disease and a higher likelihood of death [17,18]. This study demonstrated a marked decrease in adenineinduced increases in serum phosphorus, FGF-23, and parathyroid hormone levels in rats, suggesting the preventative effects of resveratrol against adenine-mediated kidney disorders.…”
Section: Discussionsupporting
confidence: 52%
“…Mineral and bone metabolism may be viewed as a complex system in which three hormones (PTH, calcitriol and FGF-23) act on three key organs (the kidneys, intestines and bones) to adjust plasma, calcium and phosphorus concentrations (19). Mineral disorders, including an increase in FGF-23 and PTH, and hyperphosphatemia, are independent risk factors in CKD progression and mortality (3,20,21). The present data revealed that ROG reduced the serum levels of FGF-23, PTH and phosphorus in the CKD rats, indicating that ROG may have a beneficial effect on the kidney through the attenuation of mineral disorders in adenine-induced CKD models.…”
Section: Discussionmentioning
confidence: 99%